2012
DOI: 10.1051/0004-6361/201116837
|View full text |Cite
|
Sign up to set email alerts
|

Deep optical observations of the massive galaxy cluster Abell 1413

Abstract: Aims. We investigate the morphology and dynamics of the massive nearby galaxy cluster Abell 1413. Methods. Using wide field imaging and spectroscopic data obtained from observations at the Canada-France-Hawaii Telescope and archival SDSS data, we build a sample of more than 250 galaxies covering a region centered on the cluster and extending to its outskirts on large scales. Results. We probe the cluster morphology analyzing the projected density distribution of galaxies and find a strong variation in the elli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Schombert 1987Schombert , 1988. Early classification efforts assigned the term "cD" to those galaxies (Matthews et al 1964;Morgan & Lesh 1965) whose haloes can in extreme cases embrace the entire host galaxy cluster as in the case of Abell 1413 (Oemler 1976;Castagné et al 2012) frequently also presenting double or multiple nuclei of central galaxies (see Kormendy & Djorgovski 1989, for a discussion of the early literature). In the following, we use the term "cD" in this simple sense, irrespective of whether the halo can photometrically identified as a separate entity or not, see Bender et al (2015) for a more profound discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Schombert 1987Schombert , 1988. Early classification efforts assigned the term "cD" to those galaxies (Matthews et al 1964;Morgan & Lesh 1965) whose haloes can in extreme cases embrace the entire host galaxy cluster as in the case of Abell 1413 (Oemler 1976;Castagné et al 2012) frequently also presenting double or multiple nuclei of central galaxies (see Kormendy & Djorgovski 1989, for a discussion of the early literature). In the following, we use the term "cD" in this simple sense, irrespective of whether the halo can photometrically identified as a separate entity or not, see Bender et al (2015) for a more profound discussion.…”
Section: Introductionmentioning
confidence: 99%
“…These previous studies at different wavelengths showed that the properties of A1413 are intermediate between classical relaxed and merging clusters. From the morphological point of view, it shows a high ellip-ticity confirmed by both optical (Castagné et al 2012) and X-ray (Pratt & Arnaud 2002) studies. The cluster is elongated approximately in the North-South direction (Fig.…”
Section: Introductionmentioning
confidence: 71%
“…The cluster is elongated approximately in the North-South direction (Fig. 7 of Castagné et al 2012). Studying the galaxy number density distribution, Castagné et al (2012) estimated the value of the cluster ellipticity ∼ 0.35 at large radii, increasing up to ∼0.8 at the cluster center r < 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schombert 1987Schombert , 1988. Early classification efforts assigned the term 'cD' to those galaxies (Matthews et al 1964;Morgan & Lesh 1965) whose halos can in extreme cases embrace the entire host galaxy cluster as in the case of Abell 1413 (Oemler 1976;Castagné et al 2012) frequently also presenting double or multiple nuclei of central galaxies (see Kormendy & Djorgovski 1989, for a discussion of the early literature). In the following, we use the term 'cD' in this simple sense, irrespective of whether the halo can photometrically identified as a separate entity or not, see Bender et al (2015) for a more profound discussion.…”
Section: Introductionmentioning
confidence: 99%